(m+-8)(m+17)=0

Simple and best practice solution for (m+-8)(m+17)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m+-8)(m+17)=0 equation:



(m+-8)(m+17)=0
We add all the numbers together, and all the variables
(m-8)(m+17)=0
We multiply parentheses ..
(+m^2+17m-8m-136)=0
We get rid of parentheses
m^2+17m-8m-136=0
We add all the numbers together, and all the variables
m^2+9m-136=0
a = 1; b = 9; c = -136;
Δ = b2-4ac
Δ = 92-4·1·(-136)
Δ = 625
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{625}=25$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-25}{2*1}=\frac{-34}{2} =-17 $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+25}{2*1}=\frac{16}{2} =8 $

See similar equations:

| 8.5=6.5{2d-3}=1 | | 10y-2=6y-30y+ | | 13y+25=0 | | 0.06(y-7)+0.02y=0.18y-0.3 | | 12b+19=7b+54.B= | | 6x-10=2(x+5) | | 0.06(y-2)+0.02y=0.04y-0.5 | | 5b+8=3b+24.B= | | (x+8=25) | | 5b+8=3b+24b= | | 0.12(y-7)+0.04=0.08y-0.6 | | 3x1=81 | | 3x^+12=60 | | 2p+p-5-5=10 | | 1.1=1.2x-5.4=-10 | | 2x=12x-12 | | 5xˆ2-18x=-9 | | 16g–11g+g=6 | | X=x+7/2x+3 | | -2x-10x+12x=18 | | 7a+8B=48 | | 142=10n+8(2+n) | | 2e−3=15 | | 2x+0−9x=6x+6−4 | | 10n+8(n=2) | | 17=-8c+41 | | 3x+11=40 | | 450.8x10^3= | | 45+4b=13 | | 7+4=11+3q | | (3x+11=40)⁰ | | 3-6a=8-6a |

Equations solver categories